Study on the Sharing Behavior of Chinese Users towards Short Videos on Traditional Chinese Medicine Health in the New Media Environment - Gao, Ruiyang; Wang, Daili; Huang, Ying; Zhang, Dandan (Transactions on Economics, Business and Management Research, 2024)
By the end of 2023, the Chinese government had successively issued a series of guiding policies emphasizing the promotion of traditional Chinese medicine (TCM) culture and its integration into people's daily lives. Against the backdrop of short videos saturating people's everyday lives, health science popularization short videos have gradually become an important channel for people to obtain information, thereby providing opportunities for the promotion of TCM health culture. This study takes users of short videos on TCM health in Wuhan as the research object, and constructs a theoretical model of the influencing factors of user sharing behavior based on user attention, usage, expectations, and sharing behavior, combined with the technology acceptance and information adoption models. A series of hypotheses were proposed. A total of 188 valid questionnaires were collected through on-site surveys, and data statistical analysis was conducted using SPSS 26.0. The empirical results show that the middle-aged group aged 22-45 exhibits the most active usage and sharing behavior towards short videos on TCM health. Users' perception of usefulness, ease of use, source credibility, and video quality of short videos on TCM health all significantly influence their information adoption, and information adoption significantly influences users' sharing behavior. Based on the discussion of the results, it is suggested to promote user sharing behavior of short videos on TCM health by improving users' perception of usefulness and ease of use of the videos, encouraging the creation of high-quality videos by users through policy support, and standardizing the credibility of video sources, thereby providing suggestions for the development of TCM culture in Wuhan and promoting the construction of health culture in China.